Grading Scientific Translation: What’s a New Teacher to Do? - Clifford, Andrew (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2007)
AbstractThe author of this article outlines the development of a scoring rubric to grade scientific translations. The article begins by enumerating the assumptions that shaped his teaching initially, before demonstrating how classroom observations eventually led the author to understand that his assumptions were faulty. The experience leads to a deeper understanding of student competencies, which are used to create an instrument that helps to describe student achievement and assign it an actual grade. The author argues that the rubric plays a part in overall student learning, and he describes the development of the rubric within the context of demographic changes taking place in North American universities.